Western Apocalyptic Time and Personal Authentic Time Journal for Religion, Film and Media - Bina Nir (Journal for Religion, Film and Media, 2019)
The concept of time is culturally dependent. During different periods in the history of Western culture, differing conceptions of times competed for primacy, sometimes contradicting one another, sometimes complementing each other. Modern Westerners, I will claim, live on two timelines - a linear, historical and cultural timeline directed to the "end of days" and a personal, authentic timeline. The Bible is a central cultural source for the linear conception of time: in the entrenched Judeo-Christian Western conception, time has a beginning, "In the beginning," and an end, "in the end of days". Time is directed in its entirety to this final event, to the establishment of God's kingdom. In our modern consumer society, which is wholly concerned with personal time, collective time has lost its purpose and its reason for being preserved. The relationship to time started to gradually change from the general conceptions of linear, collective time which is external to us to a more subjective, personal conception of time. In consumerist capitalism, time becomes personal. I demonstrate the representations of these two concepts of time in the paintings of Chaya Agur.